Discurso político e cena: ethos e imagens de si na campanha eleitoral e no exercício da governança do RS - Scariot, Viviane Demetrio da Silva (2022)
This study presents as its theme the analysis of the political speech of the governor of the state of Rio Grande do Sul (RS), Eduardo Leite, in the 2018-2022 term, addressed to state public teachers. The general objective of this work is to describe and analyze the construction of the recurrent discursive ethos in political speeches, as an image of the self, deduced from enunciative scenes and semantic restrictions of the contextual situation that denote scenography in the texture of the speech of a governor of RS. The theoretical foundation brings an interdisciplinary approach through the contributions of: Clifford Geertz (2015) and Stuart Hall (2006) in relation to culture and politics; Patrick Charaudeau (2006, 2007, 2010, 2013, 2016, 2017, 2020) on political discourse; Dominique Maingueneau (1997, 2008a, 2008b, 2010, 2015, 2018, 2020) and scholars from the perspective of global semantics, scenography and ethos. The research is descriptive, bibliographical, documentary and ex-post-facto with a qualitative approach. The research corpus consists of three political speeches by the governor of RS, Eduardo Leite, published in the form of news by the newspaper Correio do Povo (RS). The analysis of the research results shows that the enunciative scenographies are identified through different linguistic clues presented in the speeches, and their main configurations are established by the enunciative time and space and by the enunciator's and the addressee's statute, with an image of the self inferred from what is circumscribed in the speeches of the political representative of RS that are the object of this research. Thus, the thesis defended here is that the discursive ethos, built in the scenographies, projects self image conciliatory/articulating in the populist Eduardo Leite's speech, governor of RS, supported by the enunciative scenes and contextual semantic restrictions.